Wheat Intercropping Enhances the Resistance of Watermelon to Fusarium Wilt - Lv, Huifang; Cao, Haishun; Nawaz, Muhammad A.; Sohail, Hamza; Huang, Yuan; Cheng, Fei; Kong, Qiusheng; Bie, Zhilong (Frontiers in Plant Science, 2018)
A fungus Fusarium oxysporum F. sp. niveum (FON) is the causal organism of Fusarium wilt in watermelon. In this study, we evaluated the effect of wheat intercropping on the Fusarium wilt of watermelon. Our results showed that wheat intercropping decreases the incidence of Fusarium wilt of watermelon, likely due to the secretion of coumaric acid from the roots of wheat that dramatically inhibits FON spore germination, sporulation, and growth. The secretion of p-hydroxybenzoic acid, ferulic acid, and cinnamic acid from the roots of watermelon stimulates FON spore germination, sporulation, and growth. The secretion of phenolic acids and organic acids from the roots of watermelon is also promoted by FON infection. However, secretion of phenolic acids and organic acids from the roots of watermelon is substantially reduced under wheat intercropping systems. FON infection increases the accumulation of free and conjugated salicylic acid (SA) in watermelon grown under wheat intercropping systems through isochorismate (ICS) and phenylalanine ammonia-lyase (PAL) pathways. Furthermore, wheat intercropping up-regulates the expression of disease-and defense-responsive genes and improves the activities of corresponding pathogenesis-related (PR) enzymes in the roots of watermelon. In conclusion, the secretion of coumaric acid from the roots of wheat and changes in the composition of phenolic acid and organic acid secretion from the roots of watermelon suppress Fusarium wilt of watermelon under wheat intercropping system. Meanwhile, wheat intercropping also enhanced the resistance of watermelon to FON by up-regulating the expression of disease-and defense-responsive genes in watermelon.